(untitled) (Papeles, 2024)
The Coronavirus (Covid 19) emergency in Argentina highlighted the multiple challenges that affect the most vulnerable social sectors in critical moments of collapse, given their historical difficulties in accessing basic services. This article focuses on the period 2020-2022, the pandemic stage, based on a qualitative design that triangulates primary and secondary sources with the development of a case study in the city of Selva, province of Santiago del Estero. The results advise about health and non-health consequences of the emergency. The research managed to reveal organizational processes at the community level and the way in which the context situation deepened pre-existing critical conditions. Furthermore, the case shows that in some places the care and isolation measures, articulated with other control devices, faced pre-existing collective processes.